Study on the effect of different build orientations to the Rapid Prototyping Systems - Ho, Shu Qi; Ibrahim, Mohd Halim Irwan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
There are several types of rapid prototyping systems in the market nowadays. So, a study which focus on the comparison between different Rapid Prototyping systems and performance in different build orientations has shown in this study. This research focus on providing general information for dimensional accuracy and tensile properties for different build orientations and relative water absorption properties between different Rapid Prototyping systems. Test specimens were fabricated in four popular commercial Rapid Prototyping systems such as Selective Laser Sintering (SLS), PolyJet, Fused Deposition Modeling (FDM), and 3D Printing (3DP). The results came out from this research can be used as a preliminary guide for users to determine optimal strategies for rapid prototyping system selection.